Glutamine and arginine: immunonutrients for improved health - Field, C. J.; Johnson, I.; Pratt, V. (Medicine & Science in Sports & Exercise, 2000)
There is considerable literature demonstrating that specific nutrients can influence immune function in health and disease. This review will examine the literature and the rational for classifying two amino acids, glutamine (gln) and arginine (arg), as "immunonutrients" during infections. An understanding of immune defenses during infections (virus, parasite, bacteria, protozoa) and metabolism of gln and arg by immune cells is necessary to understand how these nutrients can influence specific functions of the immune system. This review focuses on several key clinical studies in immunosuppressed individuals (burn patients, individuals with cancer and HIV infection, and those undergoing surgery or who have experienced major traumas) that have tested the hypothesis that the provision of gln and/or arg is beneficial to immune function and clinical outcome. These clinical studies support the dietary "essentiality" of these two nutrients for improving immune responses in most immunosuppressive states associated with high rates of infection. However, the role of these nutrients in modulating the immune changes that occur with exercise in healthy athletes demands additional experiments.